A new species of Ubychia Rost, 1893 (Coleoptera: Curculionidae: Brachycerinae) from the island Samos, Greece, with a discussion on the distribution of the genus - Hlaváč, Peter; Nakládal, Oto (Zootaxa, 2018)
The new species, Ubychia assingi sp. nov., an endogean and anophthalmous weevil is described from the Greek island Samos. A list of species of the genus is given and the distribution and a posible biogeographic scenario for the genus is discussed.